Integration of AI and Ṭahārah from Fatḥ Al-Qarīb as a New Strategy for Strengthening Fiqh Studies in Islamic Boarding Schools - Qoyyimah, Maysarotud Dinul; Sulaikho, Siti (YASIN, 2025)
This study evaluates the potential use of ChatGPT, which is one of the artificial intelligence (AI)-based chatbots, to improve the quality of learning in Islamic boarding schools. This study specifically analyzes ChatGPT's ability to search, compile, and present ṭahārah laws based on the book Fatḥ Al-Qarīb. This study also seeks to identify the advantages and disadvantages of the use of ChatGPT in the context of fiqh studies. This research applies a qualitative method and then analysis it based on the content analysis procedure developed by Philipp Mayring. The results of the study show that ChatGPT has the potential as a tool in understanding the concept of ṭahārah, especially in terms of access speed and simple information delivery. However, ChatGPT still has limitations in providing a comprehensive explanation of the concept of ṭahārah. Some of the weaknesses identified include incompleteness in classifying various types of ṭahārah, unclear criteria for mutanajjis water, errors in defining musyammas water, and inconsistencies in explaining the law of using used water wuḍū'. This research shows that ChatGPT can be an interesting tool for learning fiqh. However, further research is needed to see how well ChatGPT understands and applies fiqh laws. In addition, this study opens up opportunities to compare the performance of ChatGPT with other classic books used in Islamic boarding schools.